Water Hammer - Pandey, Bharat Raj (Journal of Advanced College of Engineering and Management, 2023)
Dynamic Pressure rise or fall in all kinds of pipelines due to the operation of the valve which are transmitting fluids are very much essential part to consider in the design of pipeline. This paper presents how to calculate these dynamic pressure waves while designing pipelines.